Modern science for better quality control of medicinal products "Towards global harmonization of 3Rs in biologicals": The report of an EPAA workshop. (July 2017) - Schutte, Katrin; Szczepanska, Anna; Halder, Marlies; Cussler, Klaus; Sauer, Ursula G.; Stirling, Catrina; Uhlrich, Sylvie; Wilk-Zasadna, Iwona; John, David; Bopst, Martin; Garbe, Joerg; Glansbeek, Harrie L.; et al.
Abstract: This article summarizes the outcome of an international workshop organized by the European Partnership for Alternative Approaches to Animal Testing (EPAA) on Modern science for better quality control of medicinal products: Towards global harmonization of 3Rs in biologicals . As regards the safety testing of biologicals, the workshop participants agreed to actively encourage the deletion of abnormal toxicity tests and target animal batch safety tests from all relevant legal requirements and guidance documents (country-specific guidelines, pharmacopoeia monographs, WHO recommendations). To facilitate the global regulatory acceptance of non-animal methods for the potency testing of, e.g., human diphtheria and tetanus vaccines and veterinary swine erysipelas vaccines, international convergence on the scientific principles of the use of appropriately validated in vitro assays for replacing in vivo methods was identified as an overarching goal. The establishment of scientific requirements for new assays was recognized as a further means to unify regulatory approaches in different jurisdictions. It was recommended to include key regulators and manufacturers early in the corresponding discussions. Manufacturers and responsible expert groups, e.g. at the European Directorate for the Quality of Medicines and Health Care of the Council of Europe or the European Medicines Agency, were invited to consider leadership for international collaboration. Highlights: This is the report of an international workshop for better quality control of biologicals. The invited participants represented international organizations, authorities from different jurisdictions and industry. Global harmonization is required to reduce animal testing for batch control testing. For safety testing, abnormal toxicity tests should be deleted without replacement. International convergence on the scientific principles for using validated non-animal potency test methods is required.